ANALISA KELAYAKAN USAHA PENGGILINGAN PADI “SRI REZEKI“ DI DESA SUMBERAGUNG KABUPATEN BANYUWANGI - Ida Rosinta; Dwiyani Sudaryanti; Abdul Wahid Mahsuni (e_Jurnal Ilmiah Riset Akuntansi, 2022)
The purpose of this study was to analyze the feasibility of the Rice Milling Business in Sumber Agung Village, Banyuwangi Regency. This research is a research with qualitative data, the data used are primary data and secondary data. Business feasibility analysis in this study uses Benefit Cost Ratio (B/C), Net Present Value (NPV), Internal Rate of Return (IRR), and Break Event Point (BEP.  Data was collected using the methods of observation, interviews, and documentation. The results of this study are based on the B/C Ratio indicator with the results of 2.57 that the Sri Rezeki milling business is profitable, based on the NPV with the results of 386,013,739, the Sri Rezeki business is feasible to operate, based on the IRR with the results of 22.3%, the business is feasible to operate. cultivated, and based on BEP with a result of 149.69, the business is in a profitable position. So overall that Sri Rezeki's rice milling business is feasible to run.Keywords : Benefit Cost Ratio (B/C), Net Present Value (NPV), Internal Rate of Return (IRR), Break Event Point (BEP)